The Function of Nominalizing Particle NO as Modifier and Nominalizer in Japanese Language Sentence - Dewi Puspitasari (IZUMI, 2020)
Particle no in Japanese language sentence has some functions as modifier, nominalizer, and feminine marker. In this research, the researcher investigated the function of particle no as modifier and nominalizer in Japanese language sentence. Referring to term used by Shibatani et al. (2017), particle no with such function is called juntai joushi no or nominalizing particle no. This research aims to grammatically elaborate the nominalization process in Japanese language sentence with marker of nominalizing particle no. Research methodology used was qualitative descriptive using data source in form of news published in NHK (2020). Data analysis was conducted using theory as stated by Morita (2013), Shibatani et al. (2017) and Shibatani & Chung (2018). Research shows the result that the nominalizing particle no serves as modifier when attached to noun or noun phrase and nominalizer when attached to verbal clause. Function of the nominalizing particle no as modifier provides additional meaning to main noun with structure which consists of additional noun, nominalizing particle no, and main noun. Additional noun is more than one. Meanwhile, the nominalizing particle no as nominalizer changes the form of verbal clause into noun phrase, so it can be topic, subject, and object in Japanese language sentence with structure of verbal clause, nominalizing particle no, and particles which mark topic, subject, or object.